Tubular phenolic resin, carbon nano tube derived from tubular phenolic resin and preparation method of carbon nano tube

The preparation of tubular phenolic resin by hydrothermal method and pyrolytic treatment is solved, and the existing carbon nanotube preparation technology is complicated and costly, and the preparation of carbon nanotubes with efficient anchoring of catalytic active components is achieved. It is suitable for a variety of high-quality carbon nanotubes Preparation of performance materials.

CN119461343APending Publication Date: 2025-02-18DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411804186.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing carbon nanotube preparation technology is complicated, costly, and it is difficult to efficiently anchor catalytically active components.

Method used

The tubular phenolic resin is prepared by hydrothermal method and carbon nanotubes are obtained by pyrolysis. The specific steps include heating to 600-800℃ under an argon atmosphere for 1-3 hours to realize cobalt nanoparticles or cobalt iron spinel nano Efficient anchoring of particles.

Benefits of technology

It realizes simple and low-cost carbon nanotube preparation and can efficiently anchor cobalt nanoparticles and cobalt iron spinel nanoparticles. It is suitable for magnetic materials, conductive composite materials, catalysis and electrochemistry fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461343A_ABST
    Figure CN119461343A_ABST
Patent Text Reader

Abstract

The invention discloses tubular phenolic resin, a carbon nanotube derived from the tubular phenolic resin and a preparation method of the carbon nanotube, and belongs to the field of carbon nanotube preparation. The preparation method comprises the following steps: firstly, preparing tubular phenolic resin RFTs by adopting a hydrothermal method, and preparing three kinds of carbon nanotubes on the basis of the tubular phenolic resin RFTs: performing pyrolysis treatment on the RFTs to obtain the carbon nanotubes; the preparation method comprises the following steps: by taking RFTs as a carrier, constructing ZIF-67 (at) RFTs wrapped by ZIF-67, and carrying out pyrolysis treatment on the ZIF-67 (at) RFTs to obtain a carbon nanotube anchored by cobalt nanoparticles; zIF-67 (at) RFTs are obtained from the RFTs, ZIF-67 and a template agent through a hydrothermal method, and the ZIF-67 (at) RFTs are subjected to pyrolysis treatment to obtain the cobalt-iron spinel nano-particle anchored carbon nano-tubes. The tubular phenolic resin and the derived carbon nanotubes thereof are successfully prepared, and the method has the advantages of high residual carbon rate, low cost, environmental friendliness and the like; efficient anchoring of the active components on the carbon nanotubes is realized, and the derived carbon nanotubes can uniformly anchor cobalt nanoparticles and ferrocobalt spinel; the reaction process can be flexibly controlled, three kinds of carbon nanotubes can be selectively synthesized, and additional reagents or equipment are not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of carbon nanotube preparation, and in particular to a tubular phenolic resin and a carbon nanotube derived therefrom and a preparation method thereof. Background Art

[0002] Carbon nanotubes are a type of nanoscale tubular material with a special structure. Based on the microstructure of carbon nanotubes, they can be divided into single-walled carbon nanotubes and multi-walled carbon nanotubes according to the number of walls in their structure. They have a series of unique physical and chemical properties. For example, carbon nanotubes have excellent electrical conductivity, which makes them important in the fields of electronic devices, sensors, energy storage, and conductive agents. They have excellent mechanical and thermal properties, so they can be used to make high-strength materials and thermal interface materials. At the same time, they can also be used as composite materials to improve the electrical conductivity, thermal conductivity, and mechanical properties of other materials.

[0003] There are many ways to prepare carbon nanotubes. Arc discharge is an earlier preparation method. The carbon nanotubes obtained by this method have high purity, but the yield is low and the cost is high. Laser ablation can be carried out at a relatively low temperature to save energy, but the equipment is complex and the cost is higher, making it difficult to achieve large-scale production. Chemical vapor deposition is a commonly used method at present. Carbon nanotubes are generated by catalyzing the decomposition of carbon source gas on the catalyst surface, but the use of catalysts will affect its purity and related properties, and growth control is still a challenge. The use of hard and soft templates to prepare carbon nanotubes is also an effective method. The hard template method usually uses hard template materials such as alumina, porous silicon, and molecular sieves, but the elimination process of the hard template may cause the collapse of the structure and affect the performance of the product. The source of the template material may also limit the wide application of such methods. Patent CN110510599A provides a thin-walled amorphous carbon nanotube and its preparation method and application. The carbon nanotube-SiO2 composite material is obtained by calcining the sulfonated polymer nanotube-SiO2 composite material, and the SiO2 is etched away by hydrofluoric acid to prepare the thin-walled amorphous carbon nanotube. Sulfonated polymer nanotubes are used as precursors in this method, which limits the range of material selection, because not all polymers are suitable for sulfonation treatment, and hydrofluoric acid etching may be dangerous, and it is difficult to ensure uniform etching. The process of preparing carbon nanotubes using electrostatic spinning technology is complicated, the yield is low, the cost is high, and it is difficult to control the structure and purity of the nanotubes. Patent CN108625040A provides a method for preparing carbon nanotube enhanced anion exchange membrane by coaxial electrospinning, which involves multiple steps, including coaxial electrospinning, solvent steam bath, hot pressing and hydroxide ion exchange, which may cause the preparation process to be more cumbersome and time-consuming, and the production cost is also high. Therefore, how to prepare carbon nanotubes in a simpler, lower cost, and more controllable way has become one of the problems we face.

[0004] In order to meet the needs of specific applications, the use of carbon nanotubes as carriers to anchor active centers has become a hot topic of research. Cobalt, as a low-cost non-precious metal, is favored in catalyst design and other industrial applications for its performance and cost-effectiveness, and is often selected as an active component. ZIF-67, as a precursor of cobalt-based catalysts, not only provides abundant active sites, but also synergizes with carbon nanotubes through its unique pore structure and stability, providing superior performance for the reaction. At the same time, cobalt iron spinel is also a material with broad application prospects in many fields such as electrocatalysis, electromagnetic materials, energy storage and conversion. Its composite with carbon materials also greatly enhances properties such as conductivity. Therefore, how to efficiently anchor cobalt nanoparticles or cobalt iron spinel to carbon nanotubes has become another aspect of our research. .

[0005] In short, how to prepare ZIF-67@RFTs in a more suitable way and use it as a basis to prepare Co@CNTs and CoFe2O4@CNTs has important practical significance. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing tubular phenolic resin and carbon nanotubes derived therefrom. The implementation of the present invention only requires simple hydrothermal treatment, which makes up for the shortcomings of complicated steps and high cost in the preparation process of carbon nanotubes, solves the problems existing in the above-mentioned carbon nanotube preparation technologies, and at the same time realizes the efficient anchoring of catalytic active components on carbon nanotubes.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom, wherein the preparation method firstly adopts a hydrothermal method to prepare tubular phenolic resin RFTs, and then prepares three types of carbon nanotubes based on the tubular phenolic resin RFTs, specifically:

[0009] The first method is to pyrolyze tubular phenolic resin RFTs in an inert atmosphere of a tubular furnace to obtain carbon nanotubes CNTs.

[0010] The second method: using tubular phenolic resin RFTs as carriers, cobalt ions are evenly anchored, and dimethylimidazole cobalt ZIF-67 is in situ grown on its surface to construct phenolic resin tubes ZIF-67@RFTs wrapped by ZIF-67; ZIF-67@RFTs are pyrolyzed in an inert atmosphere of a tubular furnace to obtain carbon nanotubes anchored by cobalt nanoparticles, namely Co@CNTs.

[0011] The third method: tubular phenolic resin RFTs, ZIF-67 and template are hydrothermally treated to obtain ZIF-67@RFTs; ZIF-67@RFTs are pyrolyzed in an inert atmosphere of a tubular furnace to obtain carbon nanotubes anchored by cobalt iron spinel nanoparticles, namely CoFe2O4@CNTs.

[0012] The pyrolysis treatment process in the preparation process of the three carbon nanotubes is as follows: in an argon atmosphere, the temperature is increased to 600-800° C. at a heating rate of 3-5° C. / min, and then kept at that temperature for 1-3 hours, and then cooled naturally.

[0013] The preparation process of the second cobalt nanoparticle-anchored carbon nanotubes, Co@CNTs, specifically comprises the following steps:

[0014] In the first step, resorcinol and formaldehyde are added to deionized water, stirred at 20-40°C for 30-60 minutes, and then a template is added and stirred for 1-2 hours, and RFTs are obtained by hydrothermal treatment, centrifugation, and vacuum drying. In which, 0.4-1.6 g of resorcinol is added to every 20 ml of deionized water, and the molar ratio of resorcinol to formaldehyde is 0.2-0.8.

[0015] The hydrothermal treatment is as follows: hydrothermal treatment at 90-110°C for 8-24h, washing with water and ethanol alternately and centrifuging. The vacuum drying temperature is 50-80°C and the time is 12-24h.

[0016] The template agent is obtained by adding methyl orange and ferric chloride hexahydrate in a mass ratio of 1:10-2:10 into 20-30 ml of water and ultrasonicating for 20-30 minutes.

[0017] The second step is to prepare the precursor ZIF-67@RFTs of Co@CNTs;

[0018] At room temperature, 0.1-0.3 g of RFTs was dissolved in 30-50 ml of methanol by ultrasonication for 30-40 min to introduce Co 2+ , ultrasonically treated for 1-2 hours, then added with methanol solution of dimethylimidazole and stirred for 12-48 hours. The mixture was washed by methanol centrifugation until the supernatant was transparent and clear, and then vacuum dried to obtain powdered ZIF-67@RFTs.

[0019] The Co 2+ The invention is provided by cobalt nitrate hexahydrate, and the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:3-1:5.

[0020] The vacuum drying temperature is 50-80°C, and the drying time is 12-24h.

[0021] In the third step, the powdered ZIF-67@RFTs were pyrolyzed in a tube furnace to obtain Co@CNTs.

[0022] The reaction principle of preparing the carbon nanotubes anchored by cobalt nanoparticles is as follows:

[0023] Resorcinol and formaldehyde undergo a condensation reaction and grow outside the formed template. As the reaction proceeds, the template degrades itself to form tubular phenolic resin RFTs. Cobalt nitrate hexahydrate is added to the methanol solution of RFTs. 2+ It will be evenly anchored on RFTs. When dimethylimidazole is added, ZIF-67 will be generated in situ, and a purple powder sample ZIF-67@RFTs with a tubular morphology will be prepared. During the heat treatment process, ZIF-67 provides a cobalt source to form cobalt nanoparticles, and the organic matter decomposes into carbon while maintaining a tubular morphology, forming carbon nanotubes anchored by cobalt nanoparticles.

[0024] The preparation process of the third cobalt iron spinel nanoparticle anchored carbon nanotubes CoFe2O4@CNTs specifically includes the following steps:

[0025] The first step is to prepare the CoFe2O4@CNTs precursor ZIF-67@RFTs;

[0026] 0.1-0.3 g ZIF-67, resorcinol and formaldehyde were added into deionized water, stirred at 20-40° C. for 30-60 min, and then the template was added and stirred for 1-2 h. Powdered ZIF-67@RFTs was obtained by hydrothermal, centrifugal and vacuum drying.

[0027] The hydrothermal treatment is: hydrothermal treatment at 90-110°C for 8-24h, washing with water and ethanol alternately and centrifuging. The vacuum drying temperature is 50-80°C and the time is 12-24h.

[0028] The template agent is obtained by adding methyl orange and ferric chloride hexahydrate in a mass ratio of 1:10-2:10 into 20-30 ml of water and ultrasonicating for 20-30 minutes.

[0029] The second step is to prepare CoFe2O4@CNTs;

[0030] The powdered ZIF-67@RFTs were pyrolyzed in a tube furnace to obtain CoFe2O4@CNTs.

[0031] The reaction principle of the above-mentioned preparation of carbon nanotubes anchored by cobalt-iron spinel nanoparticles is:

[0032] Resorcinol and formaldehyde undergo condensation reaction and grow outside the formed template. As the reaction proceeds, the template will self-degrade to form tubular phenolic resin RFTs. At the same time, ZIF-67 will grow inside and outside the tubular phenolic resin to prepare a tubular brown sample ZIF-67@RFTs. 3+ It will combine with ZIF-67, so during the heat treatment process, ZIF-67 and the template provide cobalt source and iron source respectively to form cobalt-iron spinel nanoparticles, and the organic matter decomposes into carbon and maintains the tubular morphology to form carbon nanotubes anchored by cobalt-iron spinel nanoparticles.

[0033] A tubular phenolic resin and a carbon nanotube derived therefrom are prepared by the above method, including carbon nanotubes anchored by cobalt nanoparticles or cobalt iron spinel nanoparticles, wherein the carbon nanotubes anchored by cobalt nanoparticles are Co@CNTs, which show broad application prospects in the fields of magnetic materials, conductive composite materials, catalysis, electrochemistry, etc. The carbon nanotubes anchored by cobalt iron spinel nanoparticles are CoFe2O4@CNTs, which are widely used in multiple fields such as energy conversion and energy storage, and have versatility and high efficiency.

[0034] The beneficial effects of the present invention compared with the prior art are:

[0035] (1) The present invention successfully prepares tubular phenolic resin and its derived carbon nanotubes. Phenolic resin is used as a carbon source, which has the advantages of high residual carbon rate, low cost, and environmental friendliness. It uses a simple hydrothermal method, simple equipment, relatively safe operation, and no etching is required.

[0036] (2) The present invention realizes efficient anchoring of active components on carbon nanotubes. With phenolic resin tubes as carriers, the derived carbon nanotubes can evenly anchor cobalt nanoparticles and cobalt iron spinel.

[0037] (3) The present invention can flexibly control the reaction process by simply adjusting the order of the experimental steps, thereby selectively synthesizing three types of carbon nanotubes without adding additional reagents or equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is the SEM image of the RFTs prepared in Example 1;

[0039] Figure 2 This is the SEM image of CNTs prepared in Example 1;

[0040] Figure 3 This is the SEM image of ZIF-67@RFTs prepared in Example 2;

[0041] Figure 4This is the SEM image of Co@CNTs prepared in Example 2;

[0042] Figure 5 XRD pattern of Co@CNTs prepared in Example 2;

[0043] Figure 6 This is the SEM image of ZIF-67@RFTs prepared in Example 7;

[0044] Figure 7 This is the SEM image of CoFe2O4@CNTs prepared in Example 7;

[0045] Figure 8 This is the XRD pattern of CoFe2O4@CNTs prepared in Example 7. DETAILED DESCRIPTION

[0046] The technical solution proposed in the present invention is specifically implemented in conjunction with the embodiments below. The embodiments described below are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0047] Example 1 (First Carbon Nanotube)

[0048] 1) Step 1: Preparation of RFTs

[0049] 0.8g of resorcinol and 1.34ml of formaldehyde were added to 20ml of deionized water, and the template was added after stirring at 30℃ for 30min. Stir for 1h. The solution was added to a hydrothermal kettle, hydrothermal at 100℃ for 24h, washed alternately with water and ethanol, centrifuged, and vacuum dried at 60℃ to obtain a red powder sample RFTs with a tubular morphology. The template was obtained by adding 0.04g of methyl orange and 0.4g of ferric chloride hexahydrate to 20ml of deionized water and ultrasonicating for 30min.

[0050] 2) Step 2: Preparation of CNTs

[0051] The RFTs were pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 700°C at a heating rate of 5°C / min in an argon atmosphere and kept at that temperature for 2 hours. The temperature was then naturally cooled to obtain a black powder sample CNTs with a tubular morphology.

[0052] Example 2 (Second Carbon Nanotube)

[0053] 1) Step 1: Preparation of RFTs

[0054] 0.8g of resorcinol and 1.34ml of formaldehyde were added to 20ml of deionized water, and the template was added after stirring at 30℃ for 30min. Stir for 1h. The solution was added to a hydrothermal kettle, hydrothermal at 100℃ for 24h, washed alternately with water and ethanol, centrifuged, and vacuum dried at 60℃ for 12h to obtain a red powder sample RFTs with a tubular morphology. The template was obtained by adding 0.04g of methyl orange and 0.4g of ferric chloride hexahydrate to 20ml of deionized water and ultrasonicating for 30min.

[0055] 2) Step 2: Preparation of ZIF-67@RFTs

[0056] 0.2 g RFTs was dissolved in 40 ml methanol by ultrasonic treatment for 30 min, 1.164 g cobalt nitrate hexahydrate was added, ultrasonic treatment was carried out for 1 h, and then 40 ml methanol solution containing 1.312 g dimethylimidazole was added, stirred for 24 h, and washed by methanol centrifugation until the supernatant was transparent and clear; vacuum drying was used for drying at a temperature of 60 °C and a drying time of 12 h to obtain a purple powder sample ZIF-67@RFTs with a tubular morphology.

[0057] 3) Step 3: Preparation of Co@CNTs

[0058] The powdered ZIF-67@RFTs were pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 700°C at a heating rate of 5°C / min under an argon atmosphere and kept for 2 hours. The temperature was then naturally cooled to obtain a black powder sample Co@CNTs with a tubular morphology.

[0059] Example 3 (Second Carbon Nanotube)

[0060] 1) Step 1: Preparation of RFTs

[0061] 0.4g of resorcinol and 1.34ml of formaldehyde were added to 20ml of deionized water, and the template was added after stirring at 40℃ for 60min. Stir for 2h. The solution was added to a hydrothermal kettle, hydrothermal at 110℃ for 24h, washed alternately with water and ethanol by centrifugation, and vacuum dried at 80℃ for 24h to obtain a red powder sample RFTs with a tubular morphology. The template was obtained by adding 0.08g of methyl orange and 0.4g of ferric chloride hexahydrate to 30ml of deionized water and ultrasonicating for 30min.

[0062] 2) Step 2: Preparation of ZIF-67@RFTs

[0063] 0.1g RFTs was dissolved in 30ml methanol by ultrasonic treatment for 30min, 1.164g cobalt nitrate hexahydrate was added, ultrasonic treatment was carried out for 1h, and then 40ml methanol solution containing 1.312g dimethylimidazole was added, stirred for 24h, and washed by methanol centrifugation until the supernatant was transparent and clear; vacuum drying was adopted for drying at a drying temperature of 50℃ and a drying time of 12h to obtain a purple powder sample ZIF-67@RFTs with a tubular morphology.

[0064] 3) Step 3: Preparation of Co@CNTs

[0065] The powdered ZIF-67@RFTs were pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 600°C at a heating rate of 3°C / min under an argon atmosphere and kept for 2 hours. The temperature was then naturally cooled to obtain a black powder sample Co@CNTs with a tubular morphology.

[0066] Example 4 (Second Carbon Nanotube)

[0067] 1) Step 1: Preparation of RFTs

[0068] 1.6g of resorcinol and 1.34ml of formaldehyde were added to 20ml of deionized water, and the template was added after stirring at 20℃ for 45min. Stir for 1.5h. The solution was added to a hydrothermal kettle, hydrothermal at 90℃ for 16h, washed alternately with water and ethanol by centrifugation, and vacuum dried at 50℃ for 18h to obtain a red powder sample RFTs with a tubular morphology. The template was obtained by adding 0.06g of methyl orange and 0.4g of ferric chloride hexahydrate to 20ml of deionized water and ultrasonicating for 20min.

[0069] 2) Step 2: Preparation of ZIF-67@RFTs

[0070] 0.3 g RFTs was dissolved in 50 ml methanol by ultrasonic treatment for 40 min, 1.164 g cobalt nitrate hexahydrate was added, ultrasonic treatment was carried out for 2 h, and then 40 ml methanol solution containing 1.312 g dimethylimidazole was added, stirred for 18 h, and washed by methanol centrifugation until the supernatant was transparent and clear; vacuum drying was adopted for drying at a drying temperature of 80 °C and a drying time of 24 h to obtain a purple powder sample ZIF-67@RFTs with a tubular morphology.

[0071] 3) Step 3: Preparation of Co@CNTs

[0072] The powdered ZIF-67@RFTs were pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 800°C at a heating rate of 4°C / min under an argon atmosphere and kept for 1 hour. The temperature was then naturally cooled to obtain a black powder sample Co@CNTs with a tubular morphology.

[0073] Example 5 (Second Carbon Nanotube)

[0074] 1) Step 1: Preparation of RFTs

[0075] 0.8g of resorcinol and 1.34ml of formaldehyde were added to 20ml of deionized water, and the template was added after stirring at 30℃ for 30min. Stir for 1h. The solution was added to a hydrothermal kettle, hydrothermal at 100℃ for 8h, washed alternately with water and ethanol, centrifuged, and vacuum dried at 60℃ to obtain a red powder sample RFTs with a tubular morphology. The template was obtained by adding 0.04g of methyl orange and 0.4g of ferric chloride hexahydrate to 25ml of deionized water and ultrasonicating for 25min.

[0076] 2) Step 2: Preparation of ZIF-67@RFTs

[0077] 0.2 g RFTs was dissolved in 40 ml methanol by ultrasonic treatment for 35 min, 1.164 g cobalt nitrate hexahydrate was added, ultrasonic treatment was carried out for 1.5 h, and then 40 ml methanol solution containing 1.312 g dimethylimidazole was added, stirred for 12 h, and washed by methanol centrifugation until the supernatant was transparent and clear; vacuum drying was used for drying at a temperature of 60 °C and a drying time of 18 h to obtain a purple powder sample ZIF-67@RFTs with a tubular morphology.

[0078] 3) Step 3: Preparation of Co@CNTs

[0079] The powdered ZIF-67@RFTs were pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 800°C at a heating rate of 5°C / min under an argon atmosphere and kept for 2 hours. The temperature was then naturally cooled to obtain a black powder sample Co@CNTs with a tubular morphology.

[0080] Example 6 (Second Carbon Nanotube)

[0081] 1) Step 1: Preparation of RFTs

[0082] 0.4g of resorcinol and 1.34ml of formaldehyde were added to 20ml of deionized water, and the template was added after stirring at 30℃ for 30min. Stir for 1h. The solution was added to a hydrothermal kettle, hydrothermal at 100℃ for 24h, washed alternately with water and ethanol, centrifuged, and vacuum dried at 60℃ for 12h to obtain a red powder sample RFTs with a tubular morphology. The template was obtained by adding 0.04g of methyl orange and 0.4g of ferric chloride hexahydrate to 20ml of deionized water and ultrasonicating for 30min.

[0083] 2) Step 2: Preparation of ZIF-67@RFTs

[0084] 0.2 g RFTs was dissolved in 40 ml methanol by ultrasonic treatment for 30 min, 1.164 g cobalt nitrate hexahydrate was added, ultrasonic treatment was carried out for 1 h, and then 40 ml methanol solution containing 1.312 g dimethylimidazole was added, stirred for 24 h, and washed by methanol centrifugation until the supernatant was transparent and clear; vacuum drying was adopted for drying at a drying temperature of 60 °C and a drying time of 12 h to obtain a purple powder sample ZIF-67@RFTs with a tubular morphology.

[0085] 3) Step 3: Preparation of Co@CNTs

[0086] The powdered ZIF-67@RFTs were pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 600°C at a heating rate of 5°C / min under an argon atmosphere and kept for 3 hours. The temperature was then naturally cooled to obtain a black powder sample Co@CNTs with a tubular morphology.

[0087] Example 7 (third carbon nanotube)

[0088] 1) Step 1: Preparation of ZIF-67

[0089] 2.91 g of cobalt nitrate hexahydrate and 3.28 g of dimethylimidazole were dissolved in 200 ml of methanol solution respectively, and the two were mixed after ultrasonic treatment for 30 minutes. After stirring for 30 minutes, they were allowed to stand at room temperature for 24 hours, washed by centrifugation with anhydrous methanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain ZIF-67.

[0090] 2) Step 2: Preparation of ZIF-67@RFTs

[0091] 0.2g ZIF-67, 0.8g resorcinol and 1.34ml formaldehyde were added to 20ml deionized water, stirred at 30℃ for 30min, and then the template was added. Stir for 1h. The solution was added to a hydrothermal reactor, hydrothermal at 100℃ for 24h, washed alternately with water and ethanol, centrifuged, and vacuum dried at 65℃ for 12h to obtain a tubular brown powder sample ZIF-67@RFTs. The template was obtained by adding 0.04g methyl orange and 0.4g ferric chloride hexahydrate to 20ml deionized water and ultrasonicating for 30min.

[0092] 3) Step 3: Preparation of CoFe2O4@CNTs

[0093] The powdered ZIF-67@RFTs was pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 600°C at a heating rate of 5°C / min under an argon atmosphere and kept for 2 hours. The temperature was then naturally cooled to obtain a black powder sample CoFe2O4@CNTs with a tubular morphology.

[0094] Example 8 (third carbon nanotube)

[0095] 1) Step 1: Preparation of ZIF-67

[0096] 2.91 g of cobalt nitrate hexahydrate and 3.28 g of dimethylimidazole were dissolved in 200 ml of methanol solution respectively, and the two were mixed after ultrasonic treatment for 30 minutes. After stirring for 30 minutes, they were allowed to stand at room temperature for 24 hours, washed by centrifugation with anhydrous methanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain ZIF-67.

[0097] 2) Step 2: Preparation of ZIF-67@RFTs

[0098] 0.1g ZIF-67, 0.8g resorcinol and 1.34ml formaldehyde were added to 20ml deionized water, and the template was added after stirring at 20℃ for 45min. Stir for 2h. The solution was added to a hydrothermal reactor, hydrothermal at 110℃ for 8h, washed alternately with water and ethanol by centrifugation, and vacuum dried at 50℃ for 24h to obtain a tubular brown powder sample ZIF-67@RFTs. The template was obtained by adding 0.06g methyl orange and 0.4g ferric chloride hexahydrate to 25ml deionized water and ultrasonicating for 25min.

[0099] 3) Step 3: Preparation of CoFe2O4@CNTs

[0100] The powdered ZIF-67@RFTs was pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 800°C at a heating rate of 3°C / min under an argon atmosphere and kept for 1 hour. The temperature was then naturally cooled to obtain a black powder sample CoFe2O4@CNTs with a tubular morphology.

[0101] Example 9 (third carbon nanotube)

[0102] 1) Step 1: Preparation of ZIF-67

[0103] 2.91 g of cobalt nitrate hexahydrate and 3.28 g of dimethylimidazole were dissolved in 200 ml of methanol solution respectively, and the two were mixed after ultrasonic treatment for 30 minutes. After stirring for 30 minutes, they were allowed to stand at room temperature for 24 hours, washed by centrifugation with anhydrous methanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain ZIF-67.

[0104] 2) Step 2: Preparation of ZIF-67@RFTs

[0105] 0.3g ZIF-67, 0.8g resorcinol and 1.34ml formaldehyde were added to 20ml deionized water, stirred at 40℃ for 60min, and then the template was added. Stir for 1.5h. The solution was added to a hydrothermal reactor, hydrothermal at 90℃ for 16h, washed alternately with water and ethanol by centrifugation, and vacuum dried at 80℃ for 18h to obtain a tubular brown powder sample ZIF-67@RFTs. The template was obtained by adding 0.08g methyl orange and 0.4g ferric chloride hexahydrate to 30ml deionized water and ultrasonicating for 20min.

[0106] 3) Step 3: Preparation of CoFe2O4@CNTs

[0107] The powdered ZIF-67@RFTs was pyrolyzed in a tubular furnace. During the pyrolysis treatment, the temperature was increased to 700°C at a heating rate of 4°C / min under an argon atmosphere and kept at that temperature for 3 hours. The temperature was then naturally cooled to obtain a black powder sample CoFe2O4@CNTs with a tubular morphology.

[0108] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom, characterized in that: The preparation method firstly adopts a hydrothermal method to prepare tubular phenolic resin RFTs, and then prepares three types of carbon nanotubes based on the tubular phenolic resin RFTs, specifically: The first method is to pyrolyze tubular phenolic resin RFTs in an inert atmosphere of a tube furnace to obtain carbon nanotubes CNTs; The second method: using tubular phenolic resin RFTs as carriers, uniformly anchoring cobalt ions, in situ growing dimethyl imidazolium cobalt ZIF-67 on its surface, constructing phenolic resin tubes ZIF-67@RFTs wrapped by ZIF-67; pyrolysis of ZIF-67@RFTs in a tubular furnace under an inert atmosphere to obtain carbon nanotubes anchored by cobalt nanoparticles, namely Co@CNTs; The third method: tubular phenolic resin RFTs, ZIF-67 and template are hydrothermally treated to obtain ZIF-67@RFTs; ZIF-67@RFTs are pyrolyzed in an inert atmosphere of a tubular furnace to obtain carbon nanotubes anchored by cobalt iron spinel nanoparticles, namely CoFe2O4@CNTs.

2. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 1, characterized in that: The pyrolysis treatment process in the preparation of the three carbon nanotubes is as follows: in an argon atmosphere, the temperature is increased to 600-800° C. at a heating rate of 3-5° C. / min, kept at that temperature for 1-3 hours, and then cooled naturally.

3. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 1, characterized in that: The preparation process of the second cobalt nanoparticle-anchored carbon nanotubes, Co@CNTs, comprises the following steps: In the first step, resorcinol and formaldehyde are added to deionized water, stirred at 20-40°C for 30-60 min, and then a template is added and stirred for 1-2 h, and RFTs are obtained by hydrothermal treatment, centrifugation, and vacuum drying; The second step is to prepare the precursor ZIF-67@RFTs of Co@CNTs; At room temperature, 0.1-0.3 g of RFTs was dissolved in 30-50 ml of methanol by ultrasonication for 30-40 min to introduce Co 2+ , ultrasonically for 1-2 hours, then add a methanol solution of dimethylimidazole and stir for 12-48 hours; use methanol centrifugal washing method to wash until the supernatant is transparent and clear, and then vacuum dry to obtain powdered ZIF-67@RFTs; In the third step, the powdered ZIF-67@RFTs were pyrolyzed in a tube furnace to obtain Co@CNTs.

4. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 3, characterized in that: In the first step, 0.4-1.6 g of resorcinol is added to every 20 ml of deionized water, and the molar ratio of resorcinol to formaldehyde is 0.2-0.8; the hydrothermal treatment is: hydrothermal treatment at 90-110° C. for 8-24 hours, and washing and centrifuging alternately with water and ethanol; the template is prepared by adding methyl orange and ferric chloride hexahydrate in a mass ratio of 1:10-2:10 into 20-30 ml of water, and ultrasonic treatment for 20-30 minutes; In the second step: the Co 2+ The invention is provided by cobalt nitrate hexahydrate, and the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:3-1:

5.

5. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 3, characterized in that: In the first step: the vacuum drying temperature is 50-80°C and the time is 12-24h; In the second step: the vacuum drying temperature is 50-80°C, and the drying time is 12-24h.

6. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 1, characterized in that: The third cobalt iron spinel nanoparticle anchored carbon nanotube is a preparation process of CoFe2O4@CNTs The following steps are involved: The first step is to prepare the CoFe2O4@CNTs precursor ZIF-67@RFTs; 0.1-0.3 g ZIF-67, resorcinol and formaldehyde were added into deionized water, stirred at 20-40 °C for 30-60 min, and then the template was added and stirred for 1-2 h. Powdered ZIF-67@RFTs were obtained by hydrothermal, centrifugal and vacuum drying. The second step is to prepare CoFe2O4@CNTs; The powdered ZIF-67@RFTs were pyrolyzed in a tube furnace to obtain CoFe2O4@CNTs.

7. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 6, characterized in that: In the first step, the hydrothermal treatment is: hydrothermal treatment at 90-110° C. for 8-24 hours, and washing and centrifuging alternately with water and ethanol.

8. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 6, characterized in that: The template agent is obtained by adding methyl orange and ferric chloride hexahydrate in a mass ratio of 1:10-2:10 into 20-30 ml of water and ultrasonicating for 20-30 minutes.

9. The method for preparing a tubular phenolic resin and carbon nanotubes derived therefrom according to claim 6, characterized in that: In the first step: the vacuum drying temperature is 50-80°C and the time is 12-24h.

10. A tubular phenolic resin and carbon nanotubes derived therefrom, characterized in that: The carbon nanotubes are prepared by the preparation method described in any one of claims 1 to 9, and include carbon nanotubes anchored by cobalt nanoparticles or cobalt-iron spinel nanoparticles.

Citation Information

Patent Citations

  • Method for preparing carbon nanotube reinforced anion exchange membrane through coaxial electrostatic spinning

    CN108625040A

  • Thin-walled amorphous carbon nanotube, preparation method and application thereof

    CN110510599A